Dimensions of E-Banking Services in India: Exploring the Impact of Mobile and Phone Banking on Customer Perception in the Indian Banking Sector (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In today’s business, technology has been on the predominant indicators of growth and competitiveness. The banking industry today is in the industry of its revolution. Information technology has basically been used under two different avenues in banking. One is communication and connectivity and other is business process. Today, banks have welcomed wireless and mobile technology into their boardroom to offer their customers the freedom to pay bills, planning payments while stuck in traffic jams, to receive updates on the various marketing efforts while present at a party to provide more personal and intimate relationships. Mobile phones have immense potential of conducting financial transactions thus leading the financial growth with lot of convenience and much reduced cost. The main objective of this study is to finding out customers’ perception and awareness towards service of mobile banking or phone banking in banking sector. The study is primary containing structured questionnaire with sample size 100.